2013
DOI: 10.1159/000345826
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of MicroRNAs in the Regulation of Gene Expression by Nutrients

Abstract: MicroRNAs (miRNAs) are a class of evolutionarily conserved, small non-coding RNAs of 19-24 nucleotides in length that regulate gene expression mostly at the posttranscriptional level. They are known to be involved in the control of different processes such as cell cycling, programmed cell death, cell differentiation, tumor development, metastasis, and sensing of nutrient stress. This review summarizes the evidence regarding the changes in miRNA expression that are caused by diets with a deficiency or augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 157 publications
(105 reference statements)
0
71
0
1
Order By: Relevance
“…Cells recurrently run into stresses, including oxidative stress in cancer cells, especially in poorly angiogenic core of solid tumours [135, 136], nutrient deprivation [132, 137, 138], cardiac pressure overload [139], DNA damage, and oncogenic stress, resulting mostly from exposure to UV radiation [140143] and salt imbalance [144]. …”
Section: Mirna-mediated Upregulationmentioning
confidence: 99%
“…Cells recurrently run into stresses, including oxidative stress in cancer cells, especially in poorly angiogenic core of solid tumours [135, 136], nutrient deprivation [132, 137, 138], cardiac pressure overload [139], DNA damage, and oncogenic stress, resulting mostly from exposure to UV radiation [140143] and salt imbalance [144]. …”
Section: Mirna-mediated Upregulationmentioning
confidence: 99%
“…In particular, as recently reviewed, phytochemicals and nutrients are able to influence the expression of miRNAs, a class of evolutionarily conserved small non-coding RNAs of 19-24 nucleotides that, in turn, regulate gene expression mostly at the post-transcriptional level, suppressing translation and/or reducing the stability of their target mRNAs [42]. Several polyphenols have been shown to modulate miRNAs related to metabolic homeostasis and chronic diseases.…”
Section: Mediterranean Diet Nutrients Phytochemicals and Hormesismentioning
confidence: 99%
“…A limitation of the current study may be represented by a limited sample size [39]. A randomized control study involving a larger group of participants could be suggested as it would be able to control for potentially confounding factor(s) that could interfere during the feeding periods.…”
Section: Strengths and Limitationsmentioning
confidence: 99%